Placental histopathological findings in preterm/term and early/late onset small for gestation age: Are they significant? - Rachna Agarwal (Indian Journal of Pathology and Microbiology, 2017)
We undertook a prospective comparison of placental histopathological findings in preterm versus term and early onset versus late onset small for gestation age (SGA) to find more information on the etiological aspects of this disorder. A total of 130 women with nonanomalous SGA were allocated into preterm (n = 60); term (n = 70); early onset (n = 9) and late onset (n = 121) groups. The blinded intergroup placental histopathology comparison was performed both qualitatively (type of lesion) and quantitatively (number of the lesion). All SGA placentae showed varying number of maternal underperfusion (MUP), fetal under perfusion, inflammatory, and others lesions. There was a slight higher percentage of placenta having MUP in preterm and early onset SGA. Perivillous fibrin deposition was peculiar for placenta of preterm SGA (P = 0.043). Both preterm and early onset SGA had a higher number of placental lesions, but there was no statistical difference either in type or number of the placental lesion in any of the examined groups.